INFLUENCE OF DIPLOMACY TO LANGUAGE CHANGE - Egamberdiyeva Irodaxon; Abdurasulova Diyoraxon; Jo’rayeva Xurshida (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article gives information about influence of diplomacy to language change.